Impact of pacing mode and different echocardiographic parameters on cardiac output (PADIAC) - Blessberger, Hermann; Kammler, Juergen; Kellermair, Joerg; Kiblboeck, Daniel; Nahler, Alexander; Hrncic, Denis; Saleh, Karim; Schwarz, Stefan; Reiter, Christian; Fellner, Alexander; Eppacher, Christian; Sheldon, Todd J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
The extent of the hemodynamic benefit from AV-synchronous pacing in patients with sinus rhythm and AV block is not completely understood. Thus, we systematically investigated the association of an array of echocardiographic and epidemiological parameters with the change in cardiac output depending on the stimulation mode (AV-synchronous or AV-asynchronous pacing). Patients in sinus rhythm after previous dual chamber pacemaker implantation underwent a thorough basic echocardiographic assessment of diastolic and systolic left ventricular function, and atrial function (26 echo parameters, including novel speckle tracking strain measurements). Then, stroke volume was measured with AV-synchronous (DDD) and AV-asynchronous (VVI) pacing. Each patient represented their own control, and the sequence of stroke volume measurements was randomized. In this prospective single-center study (NCT04068233, registration August 22nd 2019), we recruited 40 individuals. The stroke volume was higher in all patients when applying AV-synchronous DDD pacing (median increase 12.8 ml [16.9%], P<0.001). No echo parameter under investigation was associated with the extent of stroke volume increase in a linear regression model. Of all epidemiological variables, a history of acute myocardial infarction (AMI) was associated with an attenuated stroke volume gain in a univariate and a multivariate regression model that adjusted for confounders. A- and S-wave velocities were reduced in the AMI group. In our cohort of patients, each subject benefited from AV-synchronous DDD pacing. No single echo parameter could predict the amount of stroke volume increase. The beneficial effect of AV-synchronous pacing on stroke volume was attenuated after prior acute myocardial infarction.